Changing Gender Ratio in India : Impact on Human Capital Investment in Urban and Rural Families (2001-2021) - Sharma, Anshika; Zubíková, Adéla; Bartůsková, Lucia; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis explores the impact of changing gender ratios on intra-household human capital investment in India from 2001 to 2021, with a particular focus on differences between urban and rural households. The study integrates demographic analysis with economic theory, drawing on Becker’s household allocation model and insights from Cultural Persistence Theory to explain persistent gender disparities in education and healthcare. Using panel data from three rounds of the National Family Health Survey (NFHS), the empirical component employs a fixed effects regression model and a difference-in-differences framework to assess whether an improving gender ratio influences investments in female children. The findings reveal that, improvements in gender imbalance—especially in rural areas—are linked to increased investment in girls’ education and health. In contrast, urban households, despite greater access to services, exhibit continued gender biases driven by cultural and economic stratification. The study also evaluates the effectiveness of gender-targeted policy interventions, such as the Beti Bachao Beti Padhao scheme, and finds that while progress has been made, structural and normative barriers still constrain equitable investment. This research contributes to the broader literature by offering a temporal and spatially disaggregated view of gendered household behavior and provides empirical evidence for the policy relevance of demographic indicators in shaping developmental outcomes.
Vedoucí práce: Adéla Zubíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses